Simulation of Carbon Nanotube on-tube Metal-Semiconductor Heterojunction Electronic Properties - Satria Zulkarnaen Bisri; Lilik Hasanah; Adi Bagus Suryamas; Sukirno Sukirno (Institut Teknologi Bandung, 2006)
It has been modeled a carbon nanotubes (CNT)-based electronic device, which is a metal-semiconductor heterojunction that purely constructed from finite length of two different carbon nanotubes. It is possible since CNT possesses uniqueness in its electronic properties that it could be metallic material or semiconductor material, depends on its chirality. The modeled device is constructed from two CNTs, which possess difference in their chirality that also make differences in their electronic properties, and connected coaxially. It has been selected CNT (10,10) as metallic CNT and pyridine-like-N-doped CNT (17,0) as semiconductor CNT in order to minimize the tapering zone between them where they are connected coaxially. It has been calculated the charge distribution as well as the potential profile of the heterojunction. The calculation was done by using self-consistent method between those two parameters, in order to solve non-homogeneous Poisson’s equation. It was performed with the aid of universal density of states for CNT to calculate its charge distribution. The electron tunneling transmission coefficient, for low energy region, also has been calculated by using Wentzel-Kramer-Brillouin (WKB) approximation. From the calculation results, it is obtained that the charge distribution as well as the potential profile of this device is doping fraction dependent. It is also inferred that the WKB method is fail to be used to calculate whole of the electron tunneling coefficient in this system. It is expected that further calculation for electron tunneling coefficient in higher energy region as well as current-voltage characteristic of this system will become an interesting issue for this carbon nanotube based electronic device.